Curcumin Along With Fe3O4 Nanoparticles Improved Sperm Parameters In Rats With Testicular Ischemia: - Hashemi, Mehrdad; Zarei Moradi , Shabnam; Angaji, Seyed Abdolhamid; Salehi, Mitra (Galen Medical Journal, 2021)
Background: Ischemic/reperfusion (I/R) in testicular tissue is one reason for the worldwide increase in male infertility. In the present study, we assessed the effects of curcumin and Fe3O4 nanoparticles (NPs) on sperm parameters in rats with I/R damage. Materials and Methods: Forty-eight adult male rats were divided into two groups (n=24 per group): control and torsion/detorsion. The control and torsion/detorsion groups were divided into four subgroups include sham, Fe3O4 NPs, curcumin, and Fe3O4 NPs+curcumin. After the rats were sacrificed, semen was collected from their epididymal tissues to assess sperm viability, motility, concentration, and morphology. Results: Curcumin significantly improved viability, motility, and normal sperm morphology in rats with I/R damage compared to the control group; however, it did not have a significant effect on sperm concentration (P<0.001). Fe3O4 NPs alone decreased all sperm parameters in the control and I/R rats (P<0.001). However, concomitant administration of Fe3O4 nanoparticles with curcumin significantly improved sperm parameters in rats with I/R damage (P<0.001). Conclusion: The increase in all semen parameters in the experimental groups with concomitant use of Fe3O4 NPs plus curcumin indicated that green synthesis of NPs could be recommended for future clinical studies.